Let's not do that again [large type] - Ginder, Grant (Thorndike Press large print basic series., 2022)
"Nancy Harrison is running for Senate, and shes going to win, goddamnit. Not that thats her slogan, although it could be. Shes said all the right things. Passed all the right legislation. Chapped her lips kissing babies. Theres just one problem: her grown children. Greta and Nick Harrison are adrift. Nick is floundering in his attempts to write a musical about the life of Joan Didion (called Hello to All That!). And then theres his little sister Greta. Smart, pretty, and completely unmotivated, allowing her life to pass her by like the shoppers at the Apple store where she works. One morning the world wakes up not to Nancy making headlines, but her daughter, Greta. Shes in Paris. With extremist protestors. Throwing a bottle of champagne through a beloved bistros front window. In order to save her campaign, not to mention her daughter, Nancy and Nick must find Greta before its too late. Smart, funny and tear-jerking, Lets Not Do That Again proves that, like democracy, family is a messy, fragile thing"--"--